Solve for: 8-4(2-5x)-3(2x-3)=9+14x

Expression: $8-4\left( 2-5x \right)-3\left( 2x-3 \right)=9+14x$

Distribute $-4$ through the parentheses

$8-8+20x-3\left( 2x-3 \right)=9+14x$

Distribute $-3$ through the parentheses

$8-8+20x-6x+9=9+14x$

Since two opposites add up to $0$, remove them from the expression

$20x-6x+9=9+14x$

Cancel equal terms on both sides of the equation

$20x-6x=14x$

Collect like terms

$14x=14x$

The statement is true for any value of $x$, because both sides are identical

$x \in ℝ$